Saline-sodic soil improvers and their effect on the development of tomato (Solanum lycopersicum) - Martínez-Sias, Valeria Abigail; Martínez-Hernández, José de Jesús; Zúñiga-Estrada, Lamberto; Martínez-Montoya, Juan Felipe (Ecosistemas y Recursos Agropecuarios, 2022)
The tomato is the main vegetable of greater economic importance at international and national level, whose production is limited when it is established in saline-sodium soils and irrigated with saline water, abiotic conditions present in arid and semi-arid regions of Mexico. The objective was to evaluate the effect of elemental sulfur (S◦) and chicken manure on morphological indices, biomass production and tomato yield, grown in a saline-sodium soil and irrigated with saline water. The tomato saladette hybrid Conan USATX 2112 was established in a shade-mesh greenhouse at Moctezuma S.L.P., on saline- sodium soil; A 2x4 factorial treatment design was used, with two doses of sulfur, 750 (S1) and 1 500 kg ha−1 (S2) and four doses of chicken manure (1, 2, 3 and 4 t ha−1 ). In the plant, five non-destructive samplings were carried out at 14, 24, 30, 45, 69 days after transplantation (DAT), estimating the morphological components. In the same way, at 54, 63 and 83 DAT, destructive samplings were carried out, evaluating the total fresh and dry matter (DM), and its distribution by plant structure, weight and fruit yield. The morphological components were positively and significantly affected by the addition of 750 kg ha−1 (S1), with respect to the treatment of 1 500 kg ha−1 (S2). In treatment S1 had a higher percentage of DM in fruit (35%), while S2 only 18%. The doses of chicken manure did not show significant differences in any of the evaluated variables.